Usability Testing on Learningcare - Nurul Azura, Che Hashim (2005)
The interest in using the Internet and Web in the classroom as part of the learning environment increase dramatically. The value of e-Learning has become widely recognized and accepted. Although e-Learning systems are increasingly used, there are a number of users complaining about usability of e-Learning. The usability of e-Learning systems is one of the key features for its success. This study aims to look into usability of e-Learning application in Universiti Utara Malaysia (UUM). Two usability attributes were examined: Learnability and Ease-of-use. Usability testing method (Thinking aloud technique) was applied and been tested to the twenty lecturers from the Faculty of Information Technology (FTM). The results indicated that the system is easy to use and to learn. Eleven usability problems were identified and discussed in this study together with its recommendations for solve the problems.